Measuring child mortality in resource limited settings using alternative approaches: South African case study - Nannan, Nadine (Division of Actuarial Science, 2018)
Post the Millennium Development Goal project a significant number of countries are still faced with the challenge of monitoring child mortality. Despite numerous enquiries since 1996 to provide this basic health indicator, South Africa has experienced prolonged periods of uncertainty regarding the level and trend of infant and under-5 mortality. The thesis develops an analytical framework to review all available data sources and methods of analysis and presents the results of the four approaches adopted to measure child mortality trends. Reviewing the demographic indicators produced from seven census and survey enquiries, the overall performance and the strengths and limitations of each approach is evaluated. Poor and extremely poor quality of data for child mortality emerges as a pervasive challenge to census and survey data. The thesis presents the remarkable improvement in the completeness of birth and death registration through South Africa's CRVS system, particularly since 2000, illustrating the possibility of using CRVS data to monitor provincial child mortality in the future and highlighting statistical challenges arising from the movement of children. In conclusion, South Africa should focus on improving CRVS for purposes of monitoring childhood mortality provincially and the comprehensive evaluation of available data is a useful lesson for other upper-middle-income countries.